Comparative Analysis in Indigenous Women's Ecological Practices Across Indonesia: A Systematic Literature Review - Rahmatul Husni (Journal of Social Research, 2024)
Indigenous women in Indonesia have long practiced ecological management and sustainable resource use, deeply embedded in their cultural beliefs, traditional wisdom, and strong connection to the land. However, their specific ecological practices have been the subject of limited research, especially compared to broader studies of the relationship between gender and ethnicity in sectors such as mining. These existing studies often highlight negative impacts on women in general but focus less on the specific practices of indigenous women, especially in relation to their contributions to biodiversity conservation and sustainable use of natural resources. Recognizing this gap, this research aims to conduct an in-depth analysis of the ecological practices of indigenous women in various regions of Indonesia, focusing on their role in environmental conservation and sustainable development. The motivation for this research is to understand how these practices, shaped by cultural, traditional, and land-based relationships, contribute to ecological management and provide lessons for sustainable living. To achieve this, this study used a systematic literature review. The literature review will involve a comprehensive examination of existing academic literature, using databases such as JSTOR, Scopus, and local Indonesian research repositories. Literature selection criteria will include relevance to indigenous practices, focus on ecological management, and contribution to biodiversity conservation. Although specific findings have not been presented, the study expects to reveal a wide variety of indigenous ecological practices. This is expected to include traditional methods of land and resource management, contributions to the resilience of local ecosystems, and sustainable practices passed down from generation to generation. This study aims to highlight the important role of indigenous women in maintaining biodiversity and adapting to environmental change. A multidimensional approach that considers the institutionalization of gender and ethnicity in mining governance, as well as the role of gender and ethnic identity, will be adopted. The findings from this literature review and field study will make a significant contribution to our understanding of the rich ecological knowledge and practices of indigenous women in Indonesia. They will also highlight the importance of incorporating these practices into broader conservation and sustainability efforts, providing policy recommendations for a more inclusive and holistic environmental approach.